Opening markets for trade in services : countries and sectors in bilateral and WTO negotiations - Marchetti, Juan A. (Cambridge Univ. P. CambridgeGB, 2008)
Explores the challenges, motivations and achievements of multilateral, regional and bilateral trade negotiations. Highlights issues in important service sectors, such as distribution, energy, finance, telecommunications, air transport and the postal and audiovisual sectors, as well as areas such as cross-border trade, the movement of natural persons and government procurement. Sheds light on the state of services liberalisation and the regulation of international trade in services at the beginning of the twenty-first century.